Learning Implementation ICARE Social Simulation to Improve The Ability of Mathematical Connection - Astuti, Sri Ady; Mariani, Scolastika; Mulyono, Mulyono (Universitas Negeri Semarang, 2019)
In the PISA study, Indonesian students are still meet in solving questions focused on mathematical connections which is shown by the ability of students to use Mathematics that they learn to solve problems in everyday life. The research objectives were knowing the quality of mathematical connection skills and measuring the increase in mathematical connection ability after the model of ICARE social simulation was implemented. The type of research used is mixed methods with research designs concurrent embedded. The results of research on ICARE model learning through quality social simulation, showed the ability of mathematical connections has reached classical completeness more than 75% and students' mathematical connection ability in ICARE model learning through social simulation is higher than that of students with expository learning. Mathematical connection ability of students in the experimental class increased by 0.538 in the medium category, while students in the control class increased by 0.375 in the medium category.